Electromagnetic wave absorption properties of mesoporous Fe3O4/C nanocomposites. (August 2015) - Zou, Changwu; Yao, Yadong; Wei, Niandong; Gong, Yichao; Fu, Weidong; Wang, Meng; Jiang, Lei; Liao, Xiaoming; Yin, Guangfu; Huang, Zhongbin; Chen, Xianchun
Abstract: In this work, the mesoporous Fe3 O4 /C nanocomposites with a yolk-shell structure (Fe3 O4 @void@C) were prepared by a silica-assisted strategy, and their microstructure, magnetic properties, and microwave absorption were studied in detail. The BET surface area and the total pore volume of Fe3 O4 @void@C are 171.5 m 2  g −1 and 0.19 cm 3  g −1, respectively. The composites show a saturation magnetization of 35.4 emu/g and reduced hysteresis loss at room temperature. The Fe3 O4 @void@C nanocomposites exhibit the obvious complementarities between complex permittivity and permeability. A minimum reflection loss value of −18.1 dB was obtained for the absorber thickness reaching 2.0 mm, and even the Fe3 O4 @void@C nanocomposites possess a lower reflection loss of-10 dB under 2 GHz bandwidth. We believe that the investigations on the Fe3 O4 @void@C nanocomposite open up a route to develop a new type of composite, which is considered as a promising candidate for microwave absorber.